Exploring dilemmas and depoliticization in inclusive lawmaking: the perspective of silent agents - Rantala, Kati; Esko, Terhi; Hämäläinen, Hanna; Salminen, Janne (Routledge, 2025)
This paper explores dilemmas in the participatory and epistemic rationales for inclusive participation in lawmaking from the viewpoint of ‘silent agents’. The participatory rationale refers to participatory rights and the requirement to provide opportunities for the participation of all affected parties. The epistemic rationale pertains to obtaining policy-relevant knowledge. ‘silent agents’ are individuals who possess experiential and contextual policy-relevant knowledge based on their everyday power of agency but lack the agentic power to participate in typical consultation procedures. Some have dormant agentic power, whereas many remain fundamentally silent. Conducting critical policy analysis, we elucidate their position in lawmaking against the rationales of inclusive participation and in relation to its normative basis, such as human rights conventions and transnational regulatory guidelines. We argue that the ideal of inclusiveness in regulatory policy is unrealistic and maintained by the depoliticization of the participatory process, generated by ‘master principles’ of both equality and equity through opaque governance language. The normative basis recognizes silent agents as important knowledge holders but downgrades their dormant agentic power. Transcending epistemic injustice in lawmaking requires supporting silent agents’ epistemic agency as active constructors of intersubjective, generalizable knowledge to challenge the structures that limit them.